Drop dynamics on chemically patterned surfaces - Kusumaatmaja, H; Leopoldes, J; Dupuis, A; Yeomans, J (2006)
We compare numerical and experimental results exploring the behaviour of liquid drops moving across a surface patterned with hydrophobic and hydrophilic stripes. A lattice Boltzmann algorithm is used to solve the hydrodynamic equations of motion of the drops allowing us to investigate their behaviour as the stripe widths and the wettability contrast are altered. We explain how the motion of the drop is determined by the interplay between the driving force and the variation in surface force as the drop moves between regions of different contact angle and we find that the shape of the drops can undergo large periodic deviations from spherical. When compared, the numerical results agree well with experiments on micron-scale drops moving across substrates patterned by microcontact printing. © EDP Sciences.